Better Cotton: An Approach to Sustainable Agriculture - Noor Nabi Bhutto; Absar Mithal Jiskani; Ghulam Mustafa Nizamani (Green Engineering Society, 2022)
Cotton is the largest industrial sector in Pakistan. However, due to bad traditional practices and use of high amount pesticides, the whole industry lost about 10-15% of cotton. For reasons of socioeconomic and environmental harm, the Better Cotton Initiative (BCI) launched